IMPACT OF DIFFERENT VARIABLES ON ACADEMIC PERFORMANCE & LEARNING - Momna Shahzad; Tamseel Asim; Abbira Hassan (Universitas PGRI Madiun, 2021)
Academic performance and learning is a widely studied research area. It incorporates various aspects and can be measured through a plethora of dimensions including the performance of students in standardized tests, their grades and GPA in university courses, the rate of graduation, the rate of class participation, entrance tests of colleges, the overall class performance of students and so on. In this research we have taken blogging, reading, writing and communication skills as the independent variables on which the academic performance and learning is dependent. The population for this quantitative research was the students of National University of Science and Technology, Pakistan.